2009
DOI: 10.1158/0008-5472.can-08-2981
|View full text |Cite
|
Sign up to set email alerts
|

Non–Small Cell Lung Cancer Exhibits Transcript Overexpression of Genes Associated with Homologous Recombination and DNA Replication Pathways

Abstract: Genes involved in DNA repair and replication have been recently investigated as predictive markers of response to chemotherapy in non-small cell lung cancer (NSCLC). However, few data on the expression of these genes in tumor compared with corresponding normal lung are available. The aim of this study was to evaluate differential mRNA levels of 22 DNA repair genes of five different DNA repair pathways: direct, base excision, nucleotide excision (NER), double-strand break (DSBR), and postreplicative repair. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
39
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 33 publications
6
39
0
Order By: Relevance
“…Ordinarily, mammalian cells efficiently suppress recombination-mediated genomic rearrangements (13,14), but damage or loss of this control of recombination, combined with protracted recombination induction by environmental agents, may significantly impact the etiology of tumors in these organs. Evidence suggesting potential cancer etiology relevance for dysregulated recombination, particularly in the case of lung cancer, includes both the overexpression of recombination genes (15) and ATM defects commonly found in this tissue (16). Conversely, pediatric leukemia is thought to be driven by specific chromosomal events, rather than the gradual accumulation of malignant features caused by many years accumulating molecular genomic insults (17).…”
Section: Introductionmentioning
confidence: 99%
“…Ordinarily, mammalian cells efficiently suppress recombination-mediated genomic rearrangements (13,14), but damage or loss of this control of recombination, combined with protracted recombination induction by environmental agents, may significantly impact the etiology of tumors in these organs. Evidence suggesting potential cancer etiology relevance for dysregulated recombination, particularly in the case of lung cancer, includes both the overexpression of recombination genes (15) and ATM defects commonly found in this tissue (16). Conversely, pediatric leukemia is thought to be driven by specific chromosomal events, rather than the gradual accumulation of malignant features caused by many years accumulating molecular genomic insults (17).…”
Section: Introductionmentioning
confidence: 99%
“…These results are also consistent with the Saviozzi et al lung cancer study that found an association with Ku70 over-expression and more aggressive tumors [238]. Never disease free 22 (6) 31 (8) …”
Section: Relationships Of Cytosolic Ku Dna-binding Activities In Breasupporting
confidence: 90%
“…and Ku80 is associated with tumor progression in breast, lung, colorectal, skin, gastric and cervical carcinomas [238][239][240][241][242][243]. Ku levels in the majority of these studies were measured either by IHC or qRT-PCR.…”
Section: Correlation Of Kumentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19] Although little controversy exists regarding the association between ERCC1 and RRM1 with platinum and gemcitabine efficacy, there are recent reports of ERCC1 and RRM1 either not being significantly associated or potentially being inversely associated with the survival of NSCLC patients after a complete surgical resection. 20,21 Knowing the prognostic impact of both genes on the survival of patients not undergoing chemotherapy with a platinum agent and/or gemcitabine is important for the design and interpretation of clinical trials that incorporate both genes into a treatment decision algorithm, in particular if this treatment is given in a curative attempt in completely resected patients. Two clinical studies in patients with advanced NSCLC have already used this approach and reported a favorable disease response when treatment is selected based on gene expression.…”
mentioning
confidence: 99%